Maternal age extremes and adverse pregnancy outcomes in low-resourced settings - Nyongesa, Paul; Ekhaguere, Osayame A.; Marete, Irene; Tenge, Constance; Kemoi, Milsort; Bann, Carla M.; Bucher, Sherri L.; Patel, Archana B.; Hibberd, Patricia L.; Naqvi, Farnaz; Saleem, Sarah; Goldenberg, Robert L.; et al. (Frontiers in Global Women's Health, 2023)
Introduction: Adolescent (<20 years) and advanced maternal age (>35 years) pregnancies carry adverse risks and warrant a critical review in low-and middle-income countries where the burden of adverse pregnancy outcomes is highest.Objective: To describe the prevalence and adverse pregnancy (maternal, perinatal, and neonatal) outcomes associated with extremes of maternal age across six countries.We performed a historical cohort analysis on prospectively collected data from a population-based cohort study conducted in the Democratic Republic of Congo, Guatemala, India, Kenya, Pakistan, and Zambia between 2010 and 2020. We included pregnant women and their neonates. We describe the prevalence and adverse pregnancy outcomes associated with pregnancies in these maternal age groups (<20, 20-24, 25-29, 30-35, and >35 years). Relative risks and 95% confidence intervals of each adverse pregnancy outcome comparing each maternal age group to the reference group of 20-24 years were obtained by fitting a Poisson model adjusting for site, maternal age, parity, multiple gestations, maternal education, antenatal care, and delivery location. Analysis by region was also performed.We analyzed 602,884 deliveries; 13% (78,584) were adolescents, and 5% (28,677) were advanced maternal age (AMA). The overall maternal mortality ratio (MMR) was 147 deaths per 100,000 live births and increased with advancing maternal age: 83 in the adolescent and 298 in the AMA group. The AMA groups had the highest MMR in all regions. Adolescent pregnancy was associated with an adjusted relative risk (aRR) of 1.07 (1.02 to 1.11) for perinatal mortality and 1.13 (1.06 to 1.19) for neonatal mortality. In contrast, AMA was associated with an aRR of 2.55 (1.81 to 3.59) for maternal mortality, 1.58 (1.49 to 1.67) for perinatal mortality, and 1.30(1.20 to 1.41) for neonatal mortality, compared to pregnancy in women 20 to 24 years. This pattern was overall similar in all regions, even in the <18 and 18-19 age groups.The maternal mortality ratio in the LMICs assessed is high and increased with advancing maternal age groups. While less prevalent, AMA was associated with a higher risk of adverse maternal mortality and, like adolescence, was associated with adverse perinatal mortality with little regional variation.